AB0334 Methotrexate Reduces Hba1c in Non-Diabetic Patients with Newly Diagnosed Rheumatoid Arthritis or Psoriatic Arthritis. (10th June 2014) - Perdan-Pirkmajer, K.; Pirkmajer, S.; Hočevar, A.; Rotar, Ž.; Gašperšič, N.; Praprotnik, S.; Tomšič, M.; Ambrožič, A.
Abstract : Background: Rheumatoid arthritis (RA) and psoriatic arthritis (PsA) are associated with an increased risk of diabetes mellitus (DM). 1 In patients with RA or PsA disease-modifying anti-rheumatic drugs, including methotrexate (MTX), may exert protective metabolic effects conducive to reduced incidence of DM. 2 Whether MTX alters metabolic risk factors in non-diabetic RA and PsA patients has not been determined unequivocally. Objectives: To assess metabolic parameters during the first six months of MTX therapy in MTX-naïve patients with newly diagnosed RA or PsA. Methods: Newly diagnosed RA (2010 ACR/EULAR criteria) and PsA (CASPAR criteria) patients were included between December 2012 and June 2013. Patients with DM or hypothyroidism were excluded. The initial assessment included DAS28ESR, BMI, fasting plasma glucose and insulin, HbA1c, TSH, triglycerides, HDL, LDL and urate. Disease activity and the metabolic parameters were followed regularly by the same physician 1, 2, 3 and 6 months after MTX initiation. Uninterrupted MTX treatment with dose escalation according to the treat to target approach was required. HOMA-IR (glucose (mM) x insulin (μU/ml)/22.5), HOMA-B (20 x insulin (μU/ml)/[glucose (mM)-3.5]) and QUICKI ([log10 glucose (mg/dl) + log10 insulin (μU/ml)] –1 ) were used as surrogate indices of insulin sensitivity and β-cell function. ANOVA or the Kruskal-Wallis test, followed by an appropriate post hoc test was used to establish statistical significance. Results: Inclusion criteria were fulfilled by 16 RA and 10 PsA patients (16 female, 10 male). Mean age was 52.5±12.2 (range: 27-76), BMI 28.4±4.8 kg/m 2 (range: 19.7-39.4) and the initial DAS28ESR 5.23±1.27 (range: 2.95-7.71). Fourteen patients had normal insulin sensitivity (HOMA-IR<2.5). Remission or low disease activity (DAS28ESR<3.2) was achieved in 76% after 6 months. Overall, MTX (± methylprednisolone) therapy did not alter BMI, fasting plasma glucose, insulin, triglyceride, cholesterol or urate levels. Conversely, HbA1c (%) decreased in a time-dependent manner from the baseline value of 5.80±0.29% to 5.55±0.31% (n=26, P =0.017) at 6 months. HbA1c (%) was reduced in 17 out of 26 patients. The decrease in HbA1c (%) was especially pronounced in patients with normal insulin sensitivity at inclusion (5.82±0.35% vs. 5.42±0.32%, P =0.013). HbA1c was reduced in 12 out of 14 cases in this patient group. HOMA-IR, HOMA-B and QUICKI remained unaltered in patients receiving MTX or MTX and methylprednisolone, indicating co-therapy with methylprednisolone did not impair insulin sensitivity. Conclusions: MTX reduces serum HbA1c in non-diabetic RA or PsA patients during the initial 6 months of treatment. HbA1c is an established predictor of CV risk in diabetic patients, a marker of prediabetes and, according to recent data an independent CV risk predictor in non-diabetics. 3 Taken together, our findings support a possible role of MTX in reducing DM and CV risk in RA as well as PsA patients. References: Solomon DH et al. Ann Rheum Dis. 2010; 69:2114–17. Solomon DH et al. JAMA. 2011; 305:2525-31. Schneider KT et al. PLoS ONE. 2012;7:1-7. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2995